Disinformation in Contemporary U.S. Foreign Policy: Impacts and Ethics in an Era of Fake News, Social Media, and Artificial Intelligence. (3rd September 2019) - Landon-Murray, Michael; Mujkic, Edin; Nussbaum, Brian
Abstract : Misinformation and disinformation, often in the form of fake news disseminated on social media, are proliferating in the "post-truth" era, with profound implications for public and policy discourse, political accountability and integrity, elections and governance. The United States is grappling with an information landscape eroded by deeply flawed information from a variety of sources, including Russian efforts to undermine its recent presidential election. As it struggles with these problems, the U.S. must also decide if and how to deploy political disinformation. U.S. foreign policy has made significant use of disinformation to influence politics and elections, and as emerging technologies allow new means of producing, disseminating, and amplifying disinformation, American presidents, security officials, and covert operators will weigh their use and usefulness. These technologies will also create new, largely unknown effects, the normative, practical, and governance implications of which must be scrutinized. Despite the attention now focused on disinformation, this angle has received inadequate consideration. This article argues that in rapidly shifting technological and political landscapes, disinformation programs require the highest possible degree of examination and accountability. Congress; the electorate; media; and researchers must engage in the public conversation to ensure that American democratic and ethical values inform U.S. policy.